MELESTARIKAN WARISAN RASA: ES KASTURI, MINUMAN DINGIN, PEMBAWA CERITA DAN TRADISI DARI GENERASI KE GENERASI - Nursalam , Laila; Nurul Jannah Ramadhan; Putri Thamara Utami; Serlin Astria Togito; Lily Tazkiyah; Nurhayati Nurhayati; Resti Aulia Putri; Zachri Al Hafis (CV. Denasya Smart Publisher, 2025)
Kasturi ice is a traditional beverage from Riau, made from the kasturi fruit (Mangifera casturi). This drink has a unique taste, combining sweet and sour flavors with a distinctive aroma. More than just a thirst quencher, kasturi ice is a symbol of cultural heritage that carries historical, philosophical, and social values. Amidst globalization and the rise of modern beverage products, the existence of kasturi ice has been declining. This study aims to uncover the cultural values contained in kasturi ice and explore strategies for its preservation. A qualitative approach was used through observation, interviews, and documentation of social activities. The results indicate that preserving kasturi ice can be achieved through innovative, educational, and participatory approaches to ensure its relevance in the modern era. Kasturi ice should be seen as part of the cultural identity of the Malay community in Riau that must be preserved and passed down to future generations.